Genetic Landscape of Rare Autoinflammatory Disease Variants in Qatar and Middle Eastern Populations Through the Integration of Whole-Genome and Exome Datasets - Sharma, Parul; Jain, Abhinav; Scaria, Vinod (Frontiers in Genetics, 2021)
Rare monogenic autoinflammatory diseases are a group of recurrent inflammatory genetic disorders caused due to genetic variants in over 37 genes. While a number of these disorders have been identified and reported from the Middle Eastern populations, the carrier frequency of these genetic variants in the Middle Eastern populations is not known. The availability of whole-genome and exome datasets of over a thousand individuals from Qatar persuaded us to explore the genetic epidemiology of rare autoinflammatory genetic variants. We have systematically analyzed genetic variants in genome-scale datasets from Qatar with a compendium of variants associated with autoinflammatory diseases. The variants were systematically reclassified according to the American College of Medical Genetics and Genomics guidelines for interpretation of variant pathogenicity. Our analysis identified 7 pathogenic and likely pathogenic variants with significant differences in their allele frequencies compared to the global population. The cumulative carrier frequency of these variants was found to be 2.58%. Furthermore, our analysis revealed that 5 genes implicated in rare autoinflammatory diseases were under natural selection. To our best knowledge, this is the first and comprehensive study on the population-scale analysis and genetic epidemiology for genetic variants causing rare autoinflammatory disease in Middle Eastern populations.